2017
DOI: 10.3390/molecules22061007
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Identification of Guan-Xin-Shu-Tong Capsule via a Mass Defect and Fragment Filtering Approach by High Resolution Mass Spectrometry: In Vitro and In Vivo Study

Abstract: The Guan-Xin-Shu-Tong capsule (GXSTC) is a well-known traditional Chinese medicine that is used for the treatment of coronary heart disease. Despite its common use in China, basic pharmacological research on its active components is limited. A comprehensive analytical method using quadrupole-time-of-flight mass spectrometry (Q-TOF/MS), specifically with the Triple TOF 5600 platform, was developed to characterize the compounds in the GXSTC powder itself (in vitro) as well as the active components in healthy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…Compounds 5 , 7 , and 15 were tentatively identified as protocatechuic acid ( 5 ), protocatechualdehyde ( 7 ), and pinocembrin ( 15 ) based on their fragmentation patterns. Compounds 13 and 14 exhibited [M−H] − ion at m / z 255.23247 and m / z 283.26450, respectively, which were characterized as palmitic acid ( 13 ) and stearic acid ( 14 ) according to deprotonated molecular weights, retention time, and the reference [ 22 ]. In the positive mode, all the compounds revealed protonated molecule [M+H] + in the MS spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 5 , 7 , and 15 were tentatively identified as protocatechuic acid ( 5 ), protocatechualdehyde ( 7 ), and pinocembrin ( 15 ) based on their fragmentation patterns. Compounds 13 and 14 exhibited [M−H] − ion at m / z 255.23247 and m / z 283.26450, respectively, which were characterized as palmitic acid ( 13 ) and stearic acid ( 14 ) according to deprotonated molecular weights, retention time, and the reference [ 22 ]. In the positive mode, all the compounds revealed protonated molecule [M+H] + in the MS spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, 13 of them had a high oral bioavailability (OB) in the TCMSP database, and their OB values are listed in Supplementary Table S1 . Several studies have elucidated and identified the GXSTC components using liquid chromatography/mass spectrometry (LC/MS) in vitro and in vivo ( Gao et al, 2017 ; Liu et al, 2018 ). According to their findings, the 15 main components we identified were also determined using LC/MS in vitro , and 12 of 15 main components were identified in rat plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Guanxin-Shutong capsule, a combination of Mongolian medicines and traditional herbs, has been commonly used to treat angina pectoris and coronary heart diseases in China (Li et al, 2019) (Rivera et al, 2014) at a weight ratio of 16:8:2:1:1 by weight. The major active components of GXSTC include phenolic acids, tanshinones, saponins, and others (Gao et al, 2017). In recent years, several clinical trials have further demonstrated that GXSTC has a significant clinical effect in treating ischemic stroke, and could markedly improve the nerve function of stroke patients (Wu, 2015;Shao, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…erefore, the automatic identification of defective capsules is needed during the production process. In recent years, numerous online capsule detection technologies based on computer vision have been applied [3,6,7]. For example, Qi and Jiang proposed a capsule defect detection method based on the hierarchical support vector machine to extract capsule defects in a real-time capsule defect recognition system [2].…”
Section: Introductionmentioning
confidence: 99%